Addition of superplasticizer and the effect of mixing iron powder ‎in concrete mixtures - Respati, Rida; Supiani, Ade; Antoni, Bram Wira (International Journal of Basic and Applied Sciences, 2025)
Concrete is in demand because it offers several advantages: a relatively low price, good strength, easy access to raw materials, long-lasting properties, fire resistance, and resistance to rot. ‎This research aims to compare the compressive strength quality of K250 concrete ‎under normal conditions and after adding superplasticizer and iron powder. Cube ‎tests consisting of ages 7, 14, and 28 days were carried out using concrete with ‎additional materials and iron powder with mixed variations; then, a concrete ‎compressive strength test was carried out. The research results show that the ‎maximum compressive strength of concrete without adding superplasticizer and ‎iron powder (0% mixture) is 371.85 kg/cm2. Adding 0.5% superplasticizer and ‎‎10%, 20%, and 30% iron powder can increase the maximum compressive strength ‎of concrete by 27.48%, 19.12%, and 8.36%, respectively. In conclusion, the ‎addition of superplasticizers and iron powder can increase the compressive ‎strength of concrete beyond the design compressive strength of normal K250 ‎concrete. Of the four concrete tests carried out with different mixture ‎proportions, all mixtures achieved the design strength of normal K250 concrete. ‎However, it is recommended that the use of iron powder not exceed 10% of the ‎aggregate weight because use above 10% will affect the slump value and increase ‎the weight of the concrete‎.